Otitis media with effusion after radiotherapy of the head and neck: a systematic review. (3rd August 2018) - Christensen, J. G.; Wessel, I.; Gothelf, A. B.; Homøe, P.
Abstract: Background: Otitis media (OM) and associated hearing problems may be side effects to radiotherapy of the head and neck region and affect patient quality of life. The condition is associated with the tumor location. Objective: To perform a systematic review concerning the present knowledge of the risk of OM after radiotherapy of the head and neck. Methods: A comprehensive search of PubMed and Embase was carried out between 1 October 2015 and 6 February 2017. The search strategy followed the PRISMA guideline for systematic reviews. Results: Of 597 articles 11 fulfilled the inclusion criteria. Seven were retrospective and four prospective. There were no randomized controlled trials. Eight studies concerned nasopharyngeal cancer. One study concerned cancer of the parotid gland and two studies concerned other locations of head and neck cancer. Meta-analysis could not be done due to heterogeneity between the studies. The incidence of OM varied considerably (range 8–29%). Conclusions: The incidence of OM is high after radiotherapy of cancer of the upper head and neck area and the Eustachian tube (ET) irradiation dosage seems associated with development of OM, but the literature is poor. Research is needed to designate patients at risk of developing OM after radiotherapy. Preferably through analysis of dosage relationships between the ET and middle ear, and development of OM. Reporting of OM should be per ear and follow standardized protocols of middle ear assessment before and after radiotherapy. Furthermore, there is a need to find new ways to prevent and treat radiation-induced OME, preferably through randomized controlled trials.